Influencer Marketing Strategies for Customer Reacquisition in Large Corporations - Ardiyanti, Ardiyanti (Celebes Scholar pg, 2023)
The impact of credibility and quality content of influencers as key factors of customer recovery marketing in large firms is the topic of this research. In this research, data were collected with the use of quantitative research design where questionnaires were used to gather information from the marketing professionals and customers who are usually targeted by the influencer marketing campaigns. It is established that the variables influencer credibility and content quality highly influence the rates of customer reacquisition. These audiences believed that information from trustworthy and knowledgeable influencers who also engage them positively will help appeal to their needs to come back for more of the client’s services. Relevant and engaging content boosts reacquisition attempts by creating high content quality. The use of real and influential persons, in combination with the generation of quality content showing the best repurchase rates. It is for these reasons that credibility and quality must be incorporated in influencer marketing campaigns to enhance customer reacquisition. The study offers practical implications for marketing practitioners that intend to improve their customer reacquisition efforts using influencer marketing.